PENGARUH CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Syarifudin, Syahrul; Nurhayati, Enung; Fauziah, Fitri (Jurnal Riset Keuangan dan Akuntansi, 2023)
The purpose of the research is to determine about the effect of corporate governance and financial performance to corporate social responsibility disclosure on company manufacture sector of consumer goods industry. This research use descriptive and verifikatif method with quantitative approach and 192 sample of data. The technique data analysis used in this research is panel data regression analysis. Based on the research results can be seen that foreign ownership, public ownership, managerial ownership, board of commissioners size, profitability, leverage, and liquidity simultaneous have significant effect to corporate social responsibility disclosure. partially, foreign ownership has significant positive effect to corporate social responsibility disclosure. public ownership has significant positive effect to corporate social responsibility disclosure. managerial ownership has significant positive effect to corporate social responsibility disclosure. board of commissioners size has significant positive effect to corporate social responsibility disclosure. profitability has significant positive effect to corporate social responsibility disclosure. leverage has significant positive effect to corporate social responsibility disclosure. and liquidity has significant positive effect to corporate social responsibility disclosure.Keywords         : Foreign Ownership, Public Ownership, Managerial Ownership, Board of Commissioners Size, Profitability, Leverage, Liquidity and Corporate Social Responsibility Disclosure.